Epidemiological and clinical characteristics of psittacosis among cases with complicated or atypical pulmonary infection using metagenomic next-generation sequencing: a multi-center observational study in China - Weifeng Huang; Fengge Wang; Qingqing Cai; Huiliang Xu; Dengwei Hong; Han Wu; Lu Zhou; Linjie Hu; Yihan Lu (BMC, 2023)
Abstract Background Chlamydia psittaci (C. psittaci) causes parrot fever in humans. Development of metagenomic next-generation sequencing (mNGS) enables the identification of C. psittaci. Methods This study aimed to determine the epidemiological and clinical characteristics of parrot fever cases in China. A multi-center observational study was conducted in 44 tertiary and secondary hospitals across 14 provinces and municipalities between April 2019 and October 2021. Results A total of 4545 patients with complicated or atypical pulmonary infection were included in the study, among which the prevalence of C. psittaci was determined to be 2.1% using mNGS. The prevalence of C. psittaci was further determined across demographic groups and types of specimens. It was significantly higher in patients with senior age (2.6% in those > 50 years), winter-spring (3.6%; particularly in December, January, and February), and southwestern (3.4%) and central and southern China (2.7%) (each P < 0.001). Moreover, the prevalence was the highest in bronchoalveolar lavage fluid (BALF) (2.9%), compared with sputum (1.1%) and peripheral blood specimens (0.9%). Additionally, co-infection of principal microorganisms was compared. Certain microorganisms were more likely to co-infect in parrot fever cases, such as Candida albicans in BALF (26.7%) and peripheral blood (6.3%), compared with non-parrot fever cases (19.7% and 1.3%); however, they did not significantly differ (each P > 0.05). Conclusion Parrot fever remains low in patients with complicated or atypical pulmonary infection. It is likely to occur in winter-spring and southwestern region in China. BALF may be the optimal specimen in the application of mNGS. Co-infection of multiple microorganisms should be further considered.